Pedagogical management and educational quality in high school students of two Public Schools in Peru - Ruiz Cortez , Susana (2022)
The research allowed to know the relationship between pedagogical management and educational quality, the results will be used to propose and implement improvement plans not only in these institutions but in all the institutions of the district and the Callao region, raising the educational level. The research determined the relationship between pedagogical management and the educational quality of students in the fourth and fifth grades of secondary school in two public educational institutions in Peru. The method used was descriptive, correlational, cross-sectional and quantitative, with a study sample of 113 participants who answered a survey using a questionnaire. Inferential statistics and linear regression were used for hypothesis testing. It is concluded that there is a good and significant correlation, determined by Pearson's correlation coefficient 0.566 with P = 0.00 (sig. Bilateral) between both variables. The linear regression line found indicates that both variables are correlated and that the model makes sense, that the pedagogical management variable is a variable that significantly influences educational quality. When analysing the results of the curriculum diversification dimension in relation to educational quality, a mean correlation of 0.462 was found; in the dimension organisation of pedagogical work in relation to educational quality, a weak correlation level of 0.443 was found; in the dimension educational process and technology in relation to educational quality, a mean correlation level of 0.480 was found.